The Influence of Servant Leadership Style, Work Discipline, and Organizational Culture on Employee Performance at the Ciremai Hospital in Cirebon City - Agies Nanda Abdullah; Kartono (International Journal Labs, 2026)
This research was conducted to determine the extent of the influence of servant leadership, employee discipline, and organizational culture on the work productivity of personnel at the Organization Office of Ciremai Hospital, Cirebon City. The academic concern that prompted this study was the symptom of a decline in human resource performance in recent times, which is strongly suspected to be related to leadership patterns, the level of compliance with regulations, and the cultural values rooted in the institution. Using an associative quantitative approach, data were collected using a Likert-scale questionnaire from 90 participants selected based on certain criteria (purposive sampling). All data were processed using SPSS 25 through the stages of instrument testing, assumption testing, multiple regression, and hypothesis testing. The results show that both independently and together, these three variables have a positive and significant impact on performance. Work discipline emerged as the strongest factor compared to the other two variables. Thus, this research confirms that the strength of the organizational system, reflected in servant leadership, strong discipline, and a strong culture, plays a central role in determining individual performance. Consequently, hospital management can use these findings as a strategic foundation for developing more targeted human resource development policies, while also enriching theoretical discourse in the fields of organizational behavior and human resource management.